2021
DOI: 10.1016/s2213-2600(21)00407-0
|View full text |Cite
|
Sign up to set email alerts
|

Does infection with or vaccination against SARS-CoV-2 lead to lasting immunity?

Abstract: Many nations are pursuing the rollout of SARS-CoV-2 vaccines as an exit strategy from unprecedented COVID-19related restrictions. However, the success of this strategy relies critically on the duration of protective immunity resulting from both natural infection and vaccination. SARS-CoV-2 infection elicits an adaptive immune response against a large breadth of viral epitopes, although the duration of the response varies with age and disease severity. Current evidence from case studies and large observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 195 publications
2
87
0
1
Order By: Relevance
“…It is also possible that sustained protection results from a broader diversity of T-cell immunity against different SARS-CoV-2 spike protein epitopes that emerges after infection, enhancing protection against variants and inducing long-lasting memory T-cell populations. 26 , 30 , 31 Although our finding of greater protection associated with infection-acquired immunity than with vaccine-acquired immunity has been reported by other authors, 32 , 33 others have reported that both types of immunity are equivalent 34 , 35 or that vaccine-acquired immunity is superior. 36 Although infection-acquired immunity is associated with a high level of protection, it wanes after 1 year in unvaccinated persons.…”
Section: Discussionsupporting
confidence: 49%
“…It is also possible that sustained protection results from a broader diversity of T-cell immunity against different SARS-CoV-2 spike protein epitopes that emerges after infection, enhancing protection against variants and inducing long-lasting memory T-cell populations. 26 , 30 , 31 Although our finding of greater protection associated with infection-acquired immunity than with vaccine-acquired immunity has been reported by other authors, 32 , 33 others have reported that both types of immunity are equivalent 34 , 35 or that vaccine-acquired immunity is superior. 36 Although infection-acquired immunity is associated with a high level of protection, it wanes after 1 year in unvaccinated persons.…”
Section: Discussionsupporting
confidence: 49%
“…17 Although we did not evaluate cell-mediated immunity, other studies have shown that natural infection induces a diverse polyepitopic cell-mediated immune response that targets the spike protein, nucleocapsid protein, and membrane protein. 18 Consequently, cell-mediated immunity is likely to be more durable than neutralizing antibody–mediated immunity in the context of small mutations, 19 particularly those mainly affecting the spike protein, such as those in the omicron variant. Furthermore, natural infection induces robust memory T-cell responses, including long-lived cytotoxic (CD8+) T cells, which have a half-life of 125 to 255 days.…”
Section: Discussionmentioning
confidence: 99%
“…Protection can be achieved by prior infection (irrespective of the vaccination status) or by recent vaccination, with participants who were unvaccinated or those who received a single dose of Ad26.COV.2, most of whom more than eight months prior, showing significantly lower levels of anti-spike IgG. Although we did not evaluate cell-mediated immunity and immune memory, it has been reported that after natural infection, the T-cell-mediated responses are targeted across a larger variety of epitopes than the humoral response, and therefore, might be more durable to genetic changes in viral epitopes [ 13 ]. Moreover, studies showed that the majority of CD4+ and CD8+ T-cell response to the spike protein induced by vaccination or prior natural infection cross-recognized the Omicron variant, thereby likely contributing to protection against severe disease [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%